2021
DOI: 10.18632/aging.203273
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of inflammation-based Glasgow prognostic score, platelet-lymphocyte ratio, and global registry of acute coronary events score for major cardiovascular and cerebrovascular events during hospitalization in patients with acute myocardial infarction

Abstract: Purpose: The goal of this study was to evaluate the predictive ability of the inflammation-based Glasgow Prognostic Score (GPS), platelet-lymphocyte ratio (PLR), Global Registry of Acute Coronary Events (GRACE) score and combined diagnostic models for the occurrence of major adverse cardiovascular and cerebrovascular events (MACEs) in patients with acute myocardial infarction (AMI). Methods: In this retrospective cohort study, eligible patients were required to meet the third global definition of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…A previous study also suggested that PSF 6 months after a stroke was linked to elevated plasma hs-CRP levels upon admission, and this outcome is in line with the findings of the present study [19]. Another inflammatory marker, PLR, has been recently gaining attention as an indicator that reflects the inflammatory state of the body, and is also used as a prognostic predictor in cancer patients [20][21][22], cardiovascular disease patients [23,24], stroke patients [25], and coronavirus disease-19 (COVID-19) patients. It is also attracting attention as a predictor of cytokine storm in patients infected with COVID-19 in the context of a pandemic [26,27].…”
Section: Discussionsupporting
confidence: 91%
“…A previous study also suggested that PSF 6 months after a stroke was linked to elevated plasma hs-CRP levels upon admission, and this outcome is in line with the findings of the present study [19]. Another inflammatory marker, PLR, has been recently gaining attention as an indicator that reflects the inflammatory state of the body, and is also used as a prognostic predictor in cancer patients [20][21][22], cardiovascular disease patients [23,24], stroke patients [25], and coronavirus disease-19 (COVID-19) patients. It is also attracting attention as a predictor of cytokine storm in patients infected with COVID-19 in the context of a pandemic [26,27].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, there are many indicators related to neutrophils and lymphocytes. The neutrophil-monocyte ratio (NMR) (8), the platelet-lymphocyte ratio (PLR) (9) and the lymphocyte-monocyte ratio (LMR) (10) were all important inflammation indicators for predicting adverse outcome in inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al suggested that targeting platelet-neutrophil interactions could be a new strategy for sepsis treatment (4). Furthermore, plateletlymphocyte aggregation is an important regulatory mechanism in thrombosis, inflammation, immunological reactions, and atherosclerosis (32). However, our results indicated that plateletmonocyte aggregation is a more sensitive inflammatory marker in endotoxemia than platelet-neutrophil and platelet-lymphocyte aggregations.…”
Section: Discussionmentioning
confidence: 55%